Focuses of students’ creativity in constructing quadratic functions through pattern generalization - Risit, Alexander Hendro; Sudirman; I Made Sulandra (Universitas Hamzanwadi, 2025)
Creativity is the ability of students to generate new ideas based on their initial situation. The focus of creativity in this study is on mathematical objects that capture students' attention when solving creativity test problems and producing creative solutions. This research aimed to identify student creativity's focus in constructing quadratic functions through pattern generalization. This qualitative case study, grounded in Silver's creativity framework, involved two creative 10th-grade students from a high school in Malang City. Data were gathered through tests and interviews and analyzed using data reduction, data presentation, and conclusion techniques. The findings revealed three focuses of student creativity in constructing quadratic functions through pattern generalization: focusing on intact squares or rectangles in considering the pattern generalization, focusing on separate shapes in considering pattern generalization and focusing on intersecting square shapes in considering pattern generalization. This study has not been conducted before, therefore filling a research gap and laying the foundation for a deeper understanding of how visual patterns foster students' creativity and enhance their comprehension of visual and symbolical quadratic functions.